FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER PADA KANTOR PELAYANAN PAJAK PRATAMA MATARAM TIMUR - Mikarsih, Ayu; Wardah, Sofiati; Hidayat, Surahman (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
This study aims to determine the effect of infrastructure, human resources, perceived usefulness costs, and perceived ease of use on the Computerized Accounting Information System at KPP East Mataram. This type of research used in this research is associative research. Data collection techniques in this study used a questionnaire. The sample collection technique used is the nonprobability sampling method. The types of data in this study are primary and secondary data. The results of this study indicate that the variables of infrastructure, human resources, and perceived usefulness do not affect the implementation of computer-based accounting information systems, while the cost and perceived convenience significantly influence the implementation of computerized accounting information systems.